Perlindungan Hukum terhadap Penggunaan Data Pribadi oleh Partai Politik Tanpa Izin - Fristanto, Kevin Bramantya; Fikri, Sultoni (CV. Era Digital Nusantara, 2025)
The objective of this research is to examine legal regulations concerning the misuse of personal data for political purposes. Legal protection against the unauthorized use of personal data by Political Parties (Parpol) is a crucial issue in today’s digital era. With advancements in information technology, individuals' personal data have become increasingly vulnerable to misuse and privacy violations. The protection of personal data as a Human Right (HAM) must be guaranteed by all parties, including the government and the private sector. The current situation reveals weak regulations governing the collection, storage, and use of personal data, which may lead to violations of individuals’ privacy rights. This study employs a normative juridical method with a literature review approach. The findings indicate the necessity of clear and strict legislation to protect personal data from misuse, as well as the importance of public awareness regarding their privacy rights. Through collaboration between the government, the business sector, and civil society, a secure and sustainable digital ecosystem can be fostered. Concrete steps to enhance personal data protection in Indonesia include the enactment of Law Number 27 of 2022 on Personal Data Protection (UU PDP), which is expected to provide a strong legal framework for safeguarding individual privacy in the ever-evolving digital era.